Protective and Curative Effects Of Justicia tranquebariensis (Linn) Leaves In Acetamenophen Induced Hepatotoxicity - M, Shabana Begum (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT The purpose of this study was to evaluate the protective and curative effect of Justicia tranquebariensis leaf extract (JTLE) using acetaminophen - induced liver injury in mice. The leaf extract at dosage of 500 and 1000 mg/kg exhibited significant protective effect against acetaminophen induced hepatotoxicity. Level of serum markers such as aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and total bilirubin (TB) were significantly increased in acetaminophen treated mice. Simultaneously, Justicia tranquebariensis leaf extract significantly suppressed mainly the increase in plasma activities of AST, ALT, ALP and TB concentration, which are considered as markers of liver functional state. The results of this study confirmed the protective and curative effect of the aqueous leaf extract of Justicia tranquebariensis.